Working with farmers to optimise mineral balance in grazing sheep. Issue 6 (22nd July 2022) - Clarkson, Andrea; Angell, Joe; Kendall, Nigel
Abstract : Background : Trace mineral analysis is a useful but underused tool in ruminant livestock production. Routine on‐farm use of diagnostic techniques can help to ensure animal nutritional requirements are being met through improved supplementation choices and timing of diagnostics. Aim of the article : This article discusses the practical importance of trace mineral testing and supplementation in sheep flocks. We include a case study to demonstrate how trace mineral management can be accomplished.